2018
DOI: 10.14252/foodsafetyfscj.2017020
|View full text |Cite
|
Sign up to set email alerts
|

Current Trends in Foodborne Human Listeriosis

Abstract: Human listeriosis results from the ingestion of foods contaminated with Listeria monocytogenes (Lm). About 1600 listeriosis cases are reported every year in the USA with >95% hospitalization and 15-20% death. The proportions of persons with listeriosis hospitalized and who die are very similar in Europe with slightly higher rates in Scandinavian countries. The occurrence of disease requires adaptation, survival, and usually growth of Lm in foods before consumption by members of the susceptible population. Desp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…The only product samples available for enumeration during this investigation indicated results below the detectable limits of the analysis (<0.3 MPN/g); there is insufficient information to indicate whether this finding reflects the dose consumed by those who became ill (which may be suggestive of low infective dose causing illness), as only two samples were enumerated, and consumers may have held products under conditions in which bacterial growth could have occurred. Recent research has demonstrated that low‐level contamination in food that may not support growth can still cause listeriosis in highly susceptible populations ( Datta & Burall, 2018 ). A recent review of available literature related to L. monocytogenes prevalence in frozen vegetables noted that few studies reported enumeration of L. monocytogenes in frozen vegetables and, in most of the cases, the numbers were below the limit of enumeration of the plate count procedure applied in each of the studies ( Koutsoumanis et al, 2020 ; Willis et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The only product samples available for enumeration during this investigation indicated results below the detectable limits of the analysis (<0.3 MPN/g); there is insufficient information to indicate whether this finding reflects the dose consumed by those who became ill (which may be suggestive of low infective dose causing illness), as only two samples were enumerated, and consumers may have held products under conditions in which bacterial growth could have occurred. Recent research has demonstrated that low‐level contamination in food that may not support growth can still cause listeriosis in highly susceptible populations ( Datta & Burall, 2018 ). A recent review of available literature related to L. monocytogenes prevalence in frozen vegetables noted that few studies reported enumeration of L. monocytogenes in frozen vegetables and, in most of the cases, the numbers were below the limit of enumeration of the plate count procedure applied in each of the studies ( Koutsoumanis et al, 2020 ; Willis et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, Listeria monocytogenes was the most sensitive bacterium to EO fractions from the five Veronica species (Table 5). This emerging foodborne pathogen, which has been associated with outbreaks worldwide and mortality rates as high as 20% [58], was successfully inhibited at concentrations ranging from 0.32 to 6.13 mg/mL, with V. chamaedrys, V. serpyllifolia, and V. arvensis active at concentrations below 1 mg/mL. On the other hand, S. aureus was the least sensitive among the Gram-positive bacteria with MIC values ranging from 4.89 to 42.89 mg/mL.…”
Section: Antibacterial Activity Of Five Veronica Speciesmentioning
confidence: 99%
“…This bacterial infection, listeriosis, can cause severe illness, including meningitis and sepsis when reaching the systemic circulation. As of today, 13 different L. monocytogenes serotypes have been discovered, of which type 4b, 1/2a and 1/2b have shown to be the most virulent ( Datta and Burall, 2018 ). Contaminated food also contains non-pathogenic Listeria species, making the diagnosis more difficult.…”
Section: Recombinant Antibodies Against Bacteriamentioning
confidence: 99%